Outcomes and risk factors of transported patients with extracorporeal membrane oxygenation: An ECMO center experience - Lingjuan Liu; Dingji Hu; Tong Hao; Shanshan Chen; Lei Chen; Yike Zhu; Chenhui Jin; Jing Wu; Haoya Fu; Haibo Qiu; Yi Yang; Songqiao Liu (Journal of Intensive Medicine, 2025)
Background: Extracorporeal membrane oxygenation (ECMO) has been proven to be a support method and technology for patients with cardiopulmonary failure. However, the transport of patients under ECMO support is challenging given the high-risk technical maneuvers and patient-care concerns involved. Herein, we examined the safety of ECMO during the transport of critically ill patients and its impact on mortality rates, to provide more secure and effective transport strategies in clinical practice. Method: To assess the safety of ECMO patient transport, this study conducted a retrospective analysis on critically ill adults who required ECMO support and transport at the intensive care unit (ICU) center between 2017 and 2023. The study utilized standard ECMO transport protocols and conducted a comprehensive statistical analysis of the collected clinical data and transport processes. The 28-day survival rate for ECMO patients was determined using Kaplan–Meier analysis, while logistic regression identified prognostic factors. Result: Out of 303 patients supported with ECMO, 111 (36.6%) were transported. 69.4% of the transport group were male, mean age was (42.0±17.0) years, mean body mass index was (24.4±4.6) kg/m2, and veno-arterial-ECMO accounted for 52.5%. The median transportation distance was 190 (interquartile range [IQR]: 70–260) km, and the longest distance was 8100 km. The median transit time was 180 (IQR: 100–260) min, and the maximum duration was 1720 min. No severe adverse events including death or mechanical failure occurred during transportation. The 28-day survival rate was 64.7% (n=196) and ICU survival rate was 56.1% (n=170) for the entire cohort; whereas, the 28-day survival rate was 72.1% (n=80) and ICU survival rate was 66.7% (n=74) in the transport group. A non-significant difference in 28-day survival was observed between the two groups after propensity score matching (P=0.56). Additionally, we found that acute physiology and chronic health evaluation II score (odds ratio [OR]=1.06, P <0.01), lactate levels (>5 mmol/L, OR=2.80, P=0.01), and renal replacement therapy initiation (OR=3.03, P <0.01) were associated with increased mortality risk. Conclusion: Transporting patients on ECMO between medical facilities is a safe procedure that does not increase patient mortality rates, provided it is orchestrated and executed by proficient transport teams. The prognostic outcome for these patients is predominantly influenced by their pre-existing medical conditions or by complications that may develop during the course of ECMO therapy. These results form the basis for the creation of specialized ECMO network hubs within healthcare regions.